Effects of walking speeds on lower extremity kinematic synergy in toe vertical position control: An experimental study - Liu, Xuan; Liang, Jitong; Liu, Ye (Medicine (Baltimore), 2024)
Background: This study aimed to investigate whether lower limb joints mutually compensate for each other, resulting in motor synergy that suppresses toe vertical position fluctuation, and whether walking speeds affect lower limb synergy. Methods: Seventeen male university students walked at slow (0.85 ± 0.04 m/s), medium (1.43 ± 0.05 m/s) and fast (1.99 ± 0.06 m/s) speeds on a 15-m walkway while lower limb kinematic data were collected. Uncontrolled manifold analysis was used to quantify the strength of synergy. Two-way (speed × phase) repeated-measures analysis of variance was used to analyze all dependent variables. Results: A significant speed-by-phase interaction was observed in the synergy index (SI) (P < .001). At slow walking speeds, subjects had greater SI during mid-swing (P < .001), while at fast walking speeds, they had greater SI during early-swing (P < .001). During the entire swing phase, fast walking exhibited lower SI values than medium (P = .005) and slow walking (P = .027). Conclusion: Kinematic synergy plays a crucial role in controlling toe vertical position during the swing phase, and fast walking exhibits less synergy than medium and slow walking. These findings contribute to a better understanding of the role of kinematic synergy in gait stability and have implications for the development of interventions aimed at improving gait stability and reducing the risk of falls.